The Effect of Morinda citrifolia and Arthrospira plattensis Powder on the Performance and Quality of Broiler Duck Carcasses - David Kurniawan; Citra Dewi Yulia Chistie (Indonesian Center for Animal Research and Development (ICARD), 2020)
This study was aimed to investigate performance and quality of broiler duck carcasses fed with Morinda citrifolia and Arthrospira plattensis. A total of 168 two-week-old broiler duck with an initial average body weight of 463 ± 29.38 g and a diversity of 6.35 % were randomly allotted to 7 experimental groups with 4 replications each with 6 bird per replication. Treatments were T0 (basal diet as a control), T1 (basal diet + 0.2% of Morinda citrifolia powder (MP)), T2 (basal diet + 0.5% of Arthrospira plattensis powde(AP)) , T3 (basal diet + 0.2% of MP+ 0.5% of AP), T4 (basal diet + 0.4% of MP + 0.5% of AP), T5 (basal diet + 0.2% of MP + 0.1% of AP), T6 (basal diet 0.4% of MP + 0.1% of AP). Variables measured were feed intake, body weight gain, feed conversion ratio, carcass percentage, abdominal fat, and visceral organ. Data were analyzed for variance based on a Completely Randomize Design and continued with Duncan’s multiple Range Test for differences. Result showed that the treatments did not affect (P>0.05) on feed intake, body weight gain and feed conversion ratio. The treatments also did not affect (P>0.05) carcass percentage, abdominal fat, and visceral organ. The diet did not significantly improve performance and quality of broiler duck carcasses.